Sexually Dimorphic Effects of Cannabinoid Compounds on Emotion and Cognition - Rubino, Tiziana; Parolaro, Daniela (Frontiers in Behavioral Neuroscience, 2011)
This review addresses the issue of sex differences in the response to cannabinoid compounds focusing mainly on behaviors belonging to the cognitive and emotional sphere. Sexual dimorphism exists in the different components of the endocannabinoid system. Males seem to have higher CB1 receptor binding sites than females, but females seem to possess more efficient CB1 receptors. Differences between sexes have been also observed in the metabolic processing of THC, the main psychoactive ingredient of marijuana. The consistent dimorphism in the endocannabinoid system and THC metabolism may justify at least in part the different sensitivity observed between male and female animals in different behavioral paradigms concerning emotion and cognition after treatment with cannabinoid compounds. On the basis of these observations, we would like to emphasize the need of including females in basic research and to analyze results for sex differences in epidemiological studies.